A Succession of Coinages in the Balkans: Imitation Roman Republican Denarii Overstruck on Drachms of Apollonia and Dyrrhachium - Macdonald, David (KOINON: The International Journal of Classical Numismatic Studies, 2022)
Dyrrhachium and Apollonia issued extensive series of drachms at a weight of about 3.30-3.40 g, and a diameter of 16-18 mm, from the third century BC until well into the first century BC. These drachms depict on the obverse a cow and calf along with a magistrate’s name in the nominative case and on the reverse a double stellate pattern, abbreviated city ethnic, and a second magistrate’s name in the genitive case. The date of the first issues of the Dyrrhachium and Apollonia drachms remains a matter of debate. It was long assumed that Dyrrhachium issues began in 229 BC when Rome effectively established domination over the region. Now some maintain a date as early as 270 BC for the first cow and calf drachms struck by Dyrrhachium while others argue for a much later date at or around 208 BC. It is generally acknowledged that Dyrrhachium began to strike drachms several decades earlier than Apollonia. The date of the end of the coinage is also a matter of debate, estimates varying from circa 60/55 BC to 30 BC. The most likely date is 48/7 BC during the Roman civil war. Julius Caesar occupied Apollonia, and subsequently he and Augustus favored the city. Pompey used Dyrrhachium as his base, and the city never after issued coins.